2020
DOI: 10.3390/ani10101907
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Study after 10 Years (2010–2019) of Meat Inspection Activity in a Domestic Swine Abattoir in Tuscany: The Slaughterhouse as an Epidemiological Observatory

Abstract: The activities performed by the Official Veterinarian at the slaughterhouse represent a useful source of data for the control of issues affecting human and animal health and welfare. This study analyzed the data deriving from ten years (2010–2019) of meat inspection in a pig slaughterhouse in Tuscany (Italy) to investigate the transport mortality rate and the frequencies and main causes of whole carcass and partial condemnations. In total, 1,246,309 pigs were slaughtered from 8 different regions of Central and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
39
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(46 citation statements)
references
References 40 publications
6
39
1
Order By: Relevance
“…Overall, findings of the D-categories, which reflect condemnation of the entire carcase, were reported at a frequency of 4.5%, with pleuritis (1.3%) being the most frequent individual finding. In contrast to our results, lower carcase condemnation rates have been reported in other studies, e.g., 0.03% in one Italian pig slaughterhouse [ 31 ], 0.24% in Portugal [ 33 ], or 0.35% in the United Kingdom [ 34 ]. However, the current study covered results from all slaughterhouses in the whole of Austria and, therefore, provides a fuller picture than previous studies.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Overall, findings of the D-categories, which reflect condemnation of the entire carcase, were reported at a frequency of 4.5%, with pleuritis (1.3%) being the most frequent individual finding. In contrast to our results, lower carcase condemnation rates have been reported in other studies, e.g., 0.03% in one Italian pig slaughterhouse [ 31 ], 0.24% in Portugal [ 33 ], or 0.35% in the United Kingdom [ 34 ]. However, the current study covered results from all slaughterhouses in the whole of Austria and, therefore, provides a fuller picture than previous studies.…”
Section: Discussioncontrasting
confidence: 99%
“…As in our study, previously reported causes of carcase condemnation were relatively heterogeneous and included abscesses, peritonitis, septicaemia, cachexia, and pleuritis/pneumonia [ 31 , 35 ]. Much more frequently, alterations of specific organs were recorded by these authors.…”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations